The role of critical experiences, positioning, and agency in the dynamic, emergent construction of heritage speaker selves - Serafini, Ellen J.; Roca-Ramirez, Sara I. (Studies in Second Language Learning and Teaching, 2024)
Previous research has proposed a crucial role for critical experiences in language learning to better understand how learners understand and discursively construct their self-concept (Mercer, 2011, 2016; Serafini, 2020a; Thompson, 2020). However, studies have mainly explored critical experiences in the narratives of foreign language learners of English with little attention to how heritage speakers of languages other than English (LOTE) draw on critical experiences in discursive constructions of self. To address this gap, this study aims to explore the impact of critical experiences in university heritage Spanish speakers’ self-narratives. Twenty heritage Spanish students completed a background questionnaire and peer-facilitated, video-recorded interview. Emergent, recurring themes were identified in transcribed interview data following tenets of grounded theory (Charmaz, 2006; Glaser & Strauss, 1967). Findings underscore the key role of positioning (Davies & Harré, 1990) in dynamic conceptions of self, particularly how heritage speakers (re)imagine and discursively construct past, current, and future self-states. Positioning was also linked to agency (Ahearn, 2001) in relation to students’ critical reflections on experiences of racialization and resistance to, or reproduction of, dominant language ideologies. Overall, the study provides valuable insights for (heritage) language educators seeking to enact critical pedagogical principles in their classroom and curriculum.